Konflik Sosial dalam Novel Prasetyane Wanita Karya Tulus Setyadi Kajian Sosiologi Sastra - Anatasya, Reza Diani; Sulanjari, Bambang; Sunarya, Sunarya (JISABDA: Jurnal Ilmiah Sastra dan Bahasa Daerah, Serta Pengajarannya, 2022)
The purpose of this research is to describe the social conflicts that exist in the novel Prasetyane Wanita by Tulus Setyadi. The formulation of the problem of this research is how the social form of the characters in the novel Prasetyane Wanita. The method in this research is descriptive qualitative. The research data are in the form of words, phrases, sentences, and discourses that contain social conflicts in the novel Prasetyane Wanita. The theory used is the sociology of literature with a focus on forms of social conflict. The technique of collecting data is by reading and recording data quotes that contain social conflicts in the novel Prasetyane Wanita. After the data is collected, data analysis techniques are carried out, by reducing the data, displaying the data, and drawing conclusions. The results of the study found that there were social conflicts in Prasetyane Wanita's novel consisting of three forms of social conflict; personal conflict between Yanti and Heru; the inner conflict that happened to Yanti; and the family conflict that happened to Mrs. Pangatun and Mr. Jimun. The social conflict stems from the principle of Yanti's loyalty to her husband, which is not approved by Yanti's parents, causing various conflicts. The principle of loyalty is useful in determining Yanti's choices in acting and her life guidelines which are reflected in the form of social conflict.